Reduced Body Fat and Epididymal Adipose Apelin Expression Associated With Raspberry Ketone [4-(4-Hydroxyphenyl)-2-Butanone] Weight Gain Prevention in High-Fat-Diet Fed Mice - Hao, Lihong; Bello, Nicholas T. (Frontiers in Physiology, 2021)
Raspberry ketone (RK; [4-(4-hydroxyphenyl)-2-butanone]) is a natural aromatic compound found in raspberries and other fruits. RK is synthetically produced for use as a commercial flavoring agent. In the US and other markets, RK is sold as a dietary supplement for weight control. The potential of RK to reduce or prevent excessive weight gain is unclear and could be a convergence of several different actions. This study sought to determine whether acute RK can immediately delay carbohydrate hyperglycemia and reduce gastrointestinal emptying. In addition, we explored the metabolic signature of chronic RK to prevent or remedy the metabolic effects of diet-induced weight gain. In high-fat diet (HFD; 45% fat)-fed male mice, acute oral gavage of RK (200 mg/kg) reduced hyperglycemia from an oral sucrose load (4 g/kg) at 15 min. In HFD-fed female mice, acute oral RK resulted in an increase in blood glucose at 30 min. Chronic daily oral gavage of RK (200 mg/kg) commencing with HFD access (HFD-RK) for 11 weeks resulted in less body weight gain and reduced fat mass compared with vehicle treated (HFD-Veh) and chronic RK starting 4 weeks after HFD access (HFD-RKw4) groups. Compared with a control group fed a low-fat diet (LFD; 10% fat) and dosed with vehicle (LFD-Veh), glucose AUC of an oral glucose tolerance test was increased with HFD-Veh, but not in HFD-RK or HFD-RKw4. Apelin (Apln) gene expression in epididymal white adipose tissue was increased in HFD-Veh, but reduced to LFD-Veh levels in the HFD-RK group. Peroxisome proliferator activated receptor alpha (Ppara) gene expression was increased in the hepatic tissue of HFD-RK and HFD-RKw4 groups. Overall, our findings suggest that long term daily use of RK prevents diet-induced weight gain, normalizes high-fat diet induced adipose Apln, and increases hepatic Ppara expression.